(3QSGdI GdfbGjI GdYLjHI hGdJMaI GdZQjHIs - (3YHO GdcQje Hf YKeGf GdQjaj, GdeNJajs
(3ChdgG (B:s
(3bGd GdCeGe aef CNQL GdPcQ ef GdCfKi hGRhLgG EjGg HdZ GdPi JefGg CRhGL GdPcQ hGdCfKi hGYde HCf GdShGO gh GdOdjd GdChd Ydi fJGL GdPcQ hGdCfKi s
(3BNQgG (B:s
(3hdG jbY ai GdJOHjQ GdWhjd hdPdc MOOJg GdMceGA hgh WQjbge eY eG ajg hGddg jhabc dCQTO GdCehQ dG Edg ZjQg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs